Immediate versus deferred chemotherapy after radical cystectomy in patients with pT3–pT4 or N+ M0 urothelial carcinoma of the bladder (EORTC 30994): an intergroup, open-label, randomised phase 3 trial. Issue 1 (January 2015) - Sternberg, Cora N; Skoneczna, Iwona; Kerst, J Martijn; Albers, Peter; Fossa, Sophie D; Agerbaek, Mads; Dumez, Herlinde; de Santis, Maria; Théodore, Christine; Leahy, Michael G; Chester, John D; Verbaeys, Antony; et al.
Summary Background Patients with muscle-invasive urothelial carcinoma of the bladder have poor survival after cystectomy. The EORTC 30994 trial aimed to compare immediate versus deferred cisplatin-based combination chemotherapy after radical cystectomy in patients with pT3–pT4 or N+ M0 urothelial carcinoma of the bladder. Methods This intergroup, open-label, randomised, phase 3 trial recruited patients from hospitals across Europe and Canada. Eligible patients had histologically proven urothelial carcinoma of the bladder, pT3–pT4 disease or node positive (pN1–3) M0 disease after radical cystectomy and bilateral lymphadenectomy, with no evidence of any microscopic residual disease. Within 90 days of cystectomy, patients were centrally randomly assigned (1:1) by minimisation to either immediate adjuvant chemotherapy (four cycles of gemcitabine plus cisplatin, high-dose methotrexate, vinblastine, doxorubicin, and cisplatin [high-dose MVAC], or MVAC) or six cycles of deferred chemotherapy at relapse, with stratification for institution, pT category, and lymph node status according to the number of nodes dissected. Neither patients nor investigators were masked. Overall survival was the primary endpoint; all analyses were by intention to treat. The trial was closed after recruitment of 284 of the planned 660 patients. This trial is registered with ClinicalTrials.gov, number NCT00028756. Findings From April 29, 2002, to Aug 14, 2008, 284 patients were randomly assigned (141 to immediate treatment and 143 to deferred treatment), and followed up until the data cutoff of Aug 21, 2013. After a median follow-up of 7·0 years (IQR 5·2–8·7), 66 (47%) of 141 patients in the immediate treatment group had died compared with 82 (57%) of 143 in the deferred treatment group. No significant improvement in overall survival was noted with immediate treatment when compared with deferred treatment (adjusted HR 0·78, 95% CI 0·56–1·08; p=0·13). Immediate treatment significantly prolonged progression-free survival compared with deferred treatment (HR 0·54, 95% CI 0·4–0·73, p<0·0001), with 5-year progression-free survival of 47·6% (95% CI 38·8–55·9) in the immediate treatment group and 31·8% (24·2–39·6) in the deferred treatment group. Grade 3–4 myelosuppression was reported in 33 (26%) of 128 patients who received treatment in the immediate chemotherapy group versus 24 (35%) of 68 patients who received treatment in the deferred chemotherapy group, neutropenia occurred in 49 (38%) versus 36 (53%) patients, respectively, and thrombocytopenia in 36 (28%) versus 26 (38%). Two patients died due to toxicity, one in each group. Interpretation Our data did not show a significant improvement in overall survival with immediate versus deferred chemotherapy after radical cystectomy and bilateral lymphadenectomy for patients with muscle-invasive urothelial carcinoma. However, the trial is limited in power, and it is possible that some subgroups of patients might still benefit from immediate chemotherapy. An updated individual patient data meta-analysis and biomarker research are needed to further elucidate the potential for survival benefit in subgroups of patients. Funding Lilly, Canadian Cancer Society Research.